Experimental Investigation on Micro Electrochemical Drilling of Hybrid Al/(Al2O3p-SiCp-Cp)–MMC - Singh, Charanjit (My University, 2018)
Composite material is a heterogeneous solid consisting of two or more than two different materials that are mechanically or metallurgical bonded together. The industrial applications of Al-MMC’s are gradually increasing due to of their surprising physical and mechanical properties as compared to monolithic materials. Again, physical and mechanical properties of these composites can be enhanced by adding two or more than two different reinforced materials i.e. hybriding in composite. As hybrid Al/(Al2O3p+SiCp+Cp)-MMC has three distinct reinforced abrasive particles which accessible better properties and strength to weight ratio as compared to any commercially available Al-MMC’s. The addition of Al2O3 and SiC reinforced particles with Al-matrix improves the wear resistance of the composite. Presence of carbon particles in hybrid composite reduces the coefficient of friction, enhanced resistance of wear. A composite has high damping capacity if it is made of both SiC and Gr reinforcement particles. The workpiece specimens were prepared from fabricated Al/SiC-MMC, Al/Al2O3p-MMC, Al/Cp-MMC, Al/(Al2O3p+SiCp)-MMC, Al/(Al2O3p+Cp)-MMC, Al/(SiCp+Cp)-MMC, and Al/(Al2O3p+SiCp+Cp)-MMC samples. These workpiece specimens were used for wear test and mechanical properties analysis. The liquid stir cast technique was utilized for fabrication of metal matrix composites (MMCs) samples with varying the weight fraction of reinforced particles alumina (Al2O3), silicon carbide (SiC) and carbon (C). The fabricated MMCs and hybrid MMCs samples were tested to analyze the mechanical properties and wear test. The impact load was improved by 7.42%, 11.31% and 10.58% for hybrid Al/(10 wt% Al2O3 + 10 wt% SiC + 5 wt% C)-MMC over Al/(10 wt% Al2O3 + 10 wt% SiC)-MMC, Al/(10 wt% Al2O3 + 5 wt% C)-MMC and Al/(10 wt% SiC + 5 wt% C)-MMC respectively. The hardness was improved by 30.39% and 31.41% for hybrid Al/(10 wt% Al2O3p + 10 wt% SiCp + 5 wt% Cp)-MMC over Al/(10 wt% Al2O3p + 5 wt% Cp)-MMC and Al/(10 wt% SiCp + 5 wt% Cp)-MMC respectively. From SEM micrograph of wear surface, it was noticed that some hard particles were pulled out, as a result formation of grooves. It is observed that the surface of composite Al/(10 wt% SiCp + 3 wt% Cp + 5 wt% Al2O3p)- MMC and Al/(15 wt% SiCp + 5 wt% Cp + 7.5 wt% Al2O3p)- MMC were rough with deep grooves as compared to composite specimen Al/(20 wt% SiCp + 7.5 wt% Cp + 10 wt% Al2O3p)-MMC. The surface of Al/(20 wt% SiCp + 7.5 wt% Cp + 10 wt% Al2O3p)-MMC was fine grooves. The surface of composite Al/(20 wt% SiCp + 7.5 wt% Cp + 10 wt% Al2O3p)- MMC was smooth, it may be due to the presence of carbon. It smears out during sliding and acts as a layer, protecting the specimen from direct contact with the disc as a result increase the wear resistance. However, the presence of hard and abrasive reinforcement in MMC reduces the machinability of the composites. The finishing of difficult to machine material in micro domain requires application of special technique. To fulfil the aim a special technique in machining i.e. an electrochemical micro machining (ECMM) set-up has been fabricated and utilized for micro drilling of Al/(Al2O3p+SiCp+Cp)-MMC. The feasibility test was carried out on fabricated set-up to identify the suitability of the fabricated set-up for finishing of liquid stir cast hybrid Al/(Al2O3p+SiCp+Cp)-MMC workpiece in micro domain. The developed ECMM set-up has different parameters such as DC supply voltage, supply current, pulse on time, pulse off time, electrolyte concentration and electrolyte flow rate. At high supply voltage, increase the impact of discharge energy in the machining area, this leads to increase the dissolution rate of metal thereby deteriorates the machined surface. The machined surface was poor and it may be due to the presence of small particles of sodium and chloride on the periphery of machined hole. Taguchi’s methods based design of experiments, L27 (313) orthogonal array and response surface methodology (RSM) Box–Behnken design were employed and made out the experimental planned accordingly. The percentage of contribution of each parameter was evaluated for various output quality characteristics. It was found that the parameters such as supply voltage, pulse on time and electrolyte concentration are the most significant parameters for response characteristics i.e. MRR, EWR, TC and SR. The surface roughness height, Ra (µ) increases with increase in electrolyte concentration, supply voltage and pulse on time. It may be due to the non-uniform metallic dissolution of material. The large number of ions associated in the inter electrode gap at supply of higher concentration of electrolyte and higher voltage. The material removal rate and electrode wear rate both increase with increase in supply voltage, electrolyte concentration and pulse-on time. These may be due to increase of current density, which in turn increases the ionization of electrolyte. The flow rate of electrolyte is an important parameter that directly affects the quality of micro-holes. The debris generated during micro electrochemical machining usually does not flush away when machining operation was carried out at low flow rate of electrolyte. Based on the RSM methodology, the optimal combination for multi response optimization of ECMM parameters for effective machining of hybrid Al/MMC is supply current (IP) 0.5 A, supply voltage (V) 2.03 V, pulse on time (Ton) 3.38 μs, pulse off time (Toff) 6.26 μs, electrolyte concentration (EC) 14.38 g/l, and electrolyte flow rate (Fr) 0.60 l/sec. Micro machined surface was analyzed through SEM and EDS photographs. The deposition of debris, voids and micro-cracks were identified on some of the machined surfaces. Some deeper and wider micro cracks were also identified on the machined surface and it may be due to supply of high peak current. The formation of ferropargasite chlorous compound was identified, it was due to chemical dissolution of ferrous material and reaction with sodium chloride. The micro tool worn out rate increases with increase in pulse-on time. From EDS analysis, it is noticed that the reinforced particles presence in hybrid MMC deposited on micro tool. This is due to the melting and re-solidification of hybrid Al/MMC during machining by micro sparking at high supply voltage and pulse on time.
Keywords: Micro ECM; Hybrid MMC; Micromachining; recast layer